Rare earth orthoniobate photochromics with self-activated upconversion emissions for high-performance optical storage applications. Issue 39 (21st September 2021) - Zhang, Zhen; Guo, Lingju; Sun, Haiqin; Peng, Dengfeng; Zou, Hua; Sun, Ningning; Zhang, Qiwei; Hao, Xihong
Abstract : Novel self-activated upconversion photochromics exhibit high-performance optical storage properties. Abstract : Solid-state inorganic luminescent photochromics have potential applications in high-density optical storage fields due to their good chemical and thermal stability. However, the failure in simultaneously achieving a high luminescent contrast and non-destructive readout capability restricts their practical applications. Herein, a new and unique route of avoiding the crosstalk between the photochromic absorption and luminescent excitation energy is proposed to design high-performance photochromic materials via the non-linear optical process of upconversion. The fabricated novel rare earth orthoniobate photochromics (RNbO4, where R = Yb, Er, Tm or Ho) with self-activated upconversion emissions exhibit reversible coloring-bleaching processes upon light stimuli (365 and 405 nm). Benefiting from the lower excitation energy and larger anti-Stokes shift of upconversion, the secondary absorption to an excitation energy of 980 nm can be effectively avoided. A non-destructive luminescence readout can then be realized whilst maintaining a near 100% luminescent switching contrast (99.2%), which is superior to conventional downshifting or downconversion readout approaches. A developed prototype storage memory with a single-level cell can be visually displayed in bright or dark fields by commercially available 365 nm (writing), 405 nm (erasing) and 980 nm (reading) lasers. These results provide new insights into future high-performance inorganic photochromic materials and promote their practical applications in advanced optical storage.